Existence for Certain Systems of Nonlinear Fractional Differential Equations - Zhaowen Zheng; Xiujuan Zhang; Jing Shao (Journal of Applied Mathematics)
By establishing a comparison result and using the monotone iterative technique, combining with the method of upper and lower solutions, the existence of solutions for systems of nonlinear fractional differential equations is considered. An example is given to demonstrate the applicability of our results.